2008
DOI: 10.1186/1471-2164-9-627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transcriptomic "stress response" evoked by antimycin A and oxygen deprivation in saccharomyces cerevisiae

Abstract: BackgroundAcute changes in environmental parameters (e.g., O2, pH, UV, osmolarity, nutrients, etc.) evoke a common transcriptomic response in yeast referred to as the "environmental stress response" (ESR) or "common environmental response" (CER). Why such a diverse array of insults should elicit a common transcriptional response remains enigmatic. Previous functional analyses of the networks involved have found that, in addition to up-regulating those for mitigating the specific stressor, the majority appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The stress response in galactose-grown cells has been suggested to arise from cessation of respiration, which is less significant on glucose because respiratory activity is already low under glucose repression (Lai et al, 2005). In accordance with this hypothesis, it was recently shown that exposure of galactose-grown cells to antimycin A, an inhibitor of the respiratory chain, leads to a similar transient transcriptomic response as anoxia (Lai et al, 2008). On galactose and glycerol (Dirmeier et al, 2002;Guzy et al, 2007), but not on glucose (Guzy et al, 2007), exposure to anaerobic conditions also leads to a transient oxidative stress response.…”
Section: Introductionmentioning
confidence: 90%
“…The stress response in galactose-grown cells has been suggested to arise from cessation of respiration, which is less significant on glucose because respiratory activity is already low under glucose repression (Lai et al, 2005). In accordance with this hypothesis, it was recently shown that exposure of galactose-grown cells to antimycin A, an inhibitor of the respiratory chain, leads to a similar transient transcriptomic response as anoxia (Lai et al, 2008). On galactose and glycerol (Dirmeier et al, 2002;Guzy et al, 2007), but not on glucose (Guzy et al, 2007), exposure to anaerobic conditions also leads to a transient oxidative stress response.…”
Section: Introductionmentioning
confidence: 90%
“…Studies in yeast have uncovered general stress responses, which were shown to activate similar sets of genes by various stresses [2931]. These sets of genes are known as common environmental response (CER) in Saccharomyces cerevisiae [32] or core environmental stress response (CESR) in Schizosaccharomyces pombe [33].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these secondary effects acts as a stimulus, activating a unique signaling pathway that regulates gene expression; heme depletion signals to the Hap1 pathway (Hickman and Winston 2007) while sterol depletion activates the Upc2/Ecm22 pathway (Hickman et al 2011). Furthermore, it has been suggested that some of the gene expression changes during hypoxia are due to a transient stress response (Lai et al 2008). Approximately 900 genes in the yeast genome respond to diverse types of stress and have been deemed part of the ESR (Gasch et al 2000).…”
mentioning
confidence: 99%